Measuring the Satisfaction of Student Tourists in Pokhara: An Analysis of Travel Life Domains - Sharma, Laxmi Kanta (Cognition, 2023)
Tourism is a significant global economic industry that is expanding rapidly. It is an important sector for development and reducing poverty in developing nations like Nepal. The aim of this paper is to assess the satisfaction of student tourists in Pokhara. 286 students were randomly selected from the 1000 students who visited Pokhara in the last week of December 2022 to participate in the survey. The data was collected by administering the five-point Likert scale questionnaires. Descriptive and analytical methods were used to examine the satisfaction of student tourists in Pokhara. Students who want to travel for experiences that will improve their academic and personal life have made student tourism an important niche in the tourism business. Younger tourists generally have more positive travel experiences compared to older tourists. The study finds that the majority of tourists were female and had a bachelor's degree. The respondents with a master's degree tend to rate their travel experiences more positively compared to those with a high school or bachelor's degree. This implies that education may influence tourists' perceptions and expectations, and that offering high-quality educational opportunities for tourists could lead to increased satisfaction. Therefore, it may be necessary for the tourism industry in Pokhara to adapt to the changing preferences and expectations of younger tourists to attract more visitors in the future.